Multimedia dalam Pengembangan Dakwah Islamiyah - Ahmad, Abd. Aziz (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2011)
This article addresses the role of mass media in spreading Islamic teaching among Muslim community. It is found that high technology strongly influence all aspects of human life. In other words, the development of technology leads to simplify people activities in daily lifes, including the methods of preaching Islamic teaching to the followers. The author comes to conclude that there are many strategies that can be employed in developing Islamic teaching. An example of these strategies is utilizing multimedia program. This sort of program integrates different kinds of media, such as, text, picture, animation, narration, video, and music. Another important thing of this multimedia is strengthening inter-activities which indicate that people not only get information passively but also can control the information or may choose different segment of learning. To put simply, this program generates the intense relationship between the doer and the media. This program is strongly important to develop the strategies of spreading Islamic teaching among Muslim community in order to cope with the impact of high technology.